Faktor Rendahnya Kemampuan Literasi Bahasa Anak PAUD KB Durratul Hikmah - Karmila P. Lamadang; Sitti Hadijah Nasulii; Pista Pista; Yuyun Mayasari (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2024)
This exploration is expected to describe the internal and external elements apart from the reason for the low language skills in PAUD KB DURRATUL HIKMAH Balantak Area. This exploration is a fascinating test. The test subjects consist of superiors and subordinates. Data collection techniques are equipped with perceptions, interviews. The research results show that 1) the factors causing the low reading ability of teenagers include: a) Understanding of teaching staff and training in relation to the development of school education. b) students. 2) External factors that cause students' low reading ability include: a). the family climate is less stable, especially interest in reading in the family is still low and most parents rarely take their students to the bookstore h. b) less creative experts. c) the child himself. d) the impact of sitting in front of the TV and using a cell phone.